2018
DOI: 10.21873/anticanres.13001
|View full text |Cite
|
Sign up to set email alerts
|

Whole-brain Radiation Therapy for Breast Cancer Patients with Dural Metastasis Without Concomitant Brain Metastasis and Leptomeningeal Metastasis

Abstract: Aim: To evaluate outcomes of breast cancer patients with confirmed dural metastasis (DM) alone who received whole-brain radiation therapy (WBRT). Patients and Methods: The medical records of thirty-three breast cancer patients who received WBRT to treat intracranial metastasis were retrospectively reviewed. The clinical presentation of DM-only was compared with that of brain metastasis (BM)/leptomeningeal metastasis (LM). Results: Eight patients had DM and 25 patients had BM/LM. Median survival was 12 months i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…However, prognosis of patients with DM have rarely been reported. A previous study compared the clinical presentation of patients with DM alone with that of patients with BM/LMC, reporting that the median OS was 12 months for patients with DM and 7 months for those with BM/LMC [24]. Based on a previous report and our results, DM is not significantly associated with patient survival.…”
Section: Discussionsupporting
confidence: 55%
“…However, prognosis of patients with DM have rarely been reported. A previous study compared the clinical presentation of patients with DM alone with that of patients with BM/LMC, reporting that the median OS was 12 months for patients with DM and 7 months for those with BM/LMC [24]. Based on a previous report and our results, DM is not significantly associated with patient survival.…”
Section: Discussionsupporting
confidence: 55%
“…Endometrial metastases from breast cancer tend to occur together synchronously with multi-organ metastases [5,13]. Despite treatment with adjuvant chemoradiation therapy after surgical resection, breast cancer is known to have high metastatic potential [5,13,32,39,40]. Among breast carcinomas, the invasive lobular type is most frequently associated with endometrial metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective review of 122 patients with dural metastases reported that although not statistically significant, radiation therapy tended to prolong the survival of patients [1]. Additionally, in a report of eight breast cancer patients with dural metastases who received whole-brain irradiation, no deterioration was observed in any of the patients [12]. In our patient, chemotherapy was given priority over radiotherapy since the dural metastases were partial and there were no symptoms of the central nervous system being affected at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%